Improvement of the drawing ratio of the anisotropic material behaviour under near plane strain conditions for DP600 characterized in elliptic hydraulic bulge test - Lenzen, Matthias; Merklein, Marion (Institute of Physics Publishing, 2018)
The plane strain condition is one of the most frequent reasons for failure in a deep drawing process. State of the art material models do not consider this strain state in FE simulations. Since there is only the notched tensile test to determine the first principal stress, an improved testing setup is needed to characterize the first and second principal stresses up to high deformations to determine the material behaviour under plane strain conditions. Within this contribution, an innovative testing setup is used, which induces a near plane strain regime in the specimen with an elliptical hydraulic bulge test. Experiments are carried out in rolling and transversal direction for DP600. Based on the experiments, stress and stain based material characteristics are evaluated. For validation of the setup, square cups are deep drawn, which have a plane strain area at the drawing radius which causes cracking under this strain state. Due to the highly directional dependent material behaviour, the drawing ratio can be increased by considering the anisotropic material behaviour by cutting the blank in an optimized position according to the rolling direction.
LFT Import::2019-08-05 (2315)